A large scale multi criteria suitability analysis for identifying solar development potential: A decision support approach for the state of Illinois, USA. (November 2021) - Kwak, Yoonshin; Deal, Brian; Heavisides, Tom
Abstract: The State of Illinois is examining prospects to increase the development of in-state renewable energy resources on public lands. In response, this research develops a scalable decision-support tool for identifying suitable areas for solar energy generation in the state. This paper provides guidance for state agency-driven solar development by evaluating the suitability of potential generation areas in terms of environmental impact, socioeconomic costs, and energy productivity, and providing a forum for critical decision-making. More specifically, geospatial technologies are combined with a suitability analysis to reveal the potential for solar energy generation on public lands. This study demonstrates the usefulness of the resulting information for supporting both regional and local decision-making as a Planning Support System (PSS). Our analysis suggests that the large-scale analysis using fine resolution data is useful for comparison and site-specific decision making - with site verification protocols in terms of physical implementation. We find that planning decisions for solar development should use a fine-grained suitability approach at a large scale and a feasibility analysis at a specific scale. We present our findings in statewide application along with a scalable PSS tool to optimize and support solar decision-making process and democratize the information for engaging a broader audience. Graphical abstract: Image 1